Evaluation of Trichoderma species against Fusarium oxysporum f.sp. lycopersici for biological control of tomato wilt - and MUTUM S. SINGH, T. NIRUPAMA DEVI*, LINTHOINGAMBI W. (Indian Phytopathology, 2013)
The Fusarium wilt of tomato (Lycopersicon esculentum Mill.) caused by F. oxysporum f.sp. lycopersici (Sacc. ) Snyder and Hansen is recognised as one of the most devastating disease in major tomato growing regions worldwide. For eco-friendly and sustainable management of the disease, 88 Trichoderma isolates belonging to 8 species of the genus, T. viride, T. virens, T. harzianum, T. hamatum, T. piluliferum, T. koningii, T. pseudokoningii and T. longibrachiatum were evaluated against the pathogen in dual culture and through production of volatile and non-volatile metabolites. T. viride isolate (TV19) followed by T. harzianum isolate (TH7) and T. virens isolate (TVr5) showed maximum inhibition to mycelial growth of the pathogen. The potential isolates were evaluated as seed, soil and combined seed and soil treatments in pot experiment. All the treatments resulted in significant reduction in mortality of tomato seedlings and improvement in the plant growth parameters. The highest seed germination percentage (81.11%) and control of seedling mortality (61.63%) were obtained in combined seed and soil treatment with T. viride (TV19). The isolates were evaluated under field conditions during 2010 and 2011 cropping season in randomized block design in three replications. The results showed that combined seed and soil treatment with TV19 recorded the least wilt incidence (9.30%) as compared to the control (43.49%). This treatment produced higher yield (292.61 qha-1) than control (102.64 qha-1).